A new species of Bathanthidium Mavromoustakis (Hymenoptera: Megachilidae: Anthidiini) from China, with a key to the species - Niu, Ze-Qing; Wu, Yan-Ru; Zhu, Chao-Dong (Zootaxa, 2012)
Bathanthidium hainanense sp. nov. from Wuzhi Mountain, Hainan, China is described and illustrated. A key to the eightspecies of the genus is presented. Bathanthidium (B.) circinatum Wu, 2004 is transferred to the subgenus B. (Stenanthi- diellum), new comb.